2011
DOI: 10.1120/jacmp.v12i4.3589
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐specific CT dosimetry calculation: a feasibility study

Abstract: Current estimation of radiation dose from computed tomography (CT) scans on patients has relied on the measurement of Computed Tomography Dose Index (CTDI) in standard cylindrical phantoms, and calculations based on mathematical representations of “standard man”. Radiation dose to both adult and pediatric patients from a CT scan has been a concern, as noted in recent reports. The purpose of this study was to investigate the feasibility of adapting a radiation treatment planning system (RTPS) to provide patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…It has already been shown by others [22] that the direct measurements of CT dose in a Rando phantom are up to 40% higher than the MC technique.…”
Section: Resultsmentioning
confidence: 91%
“…It has already been shown by others [22] that the direct measurements of CT dose in a Rando phantom are up to 40% higher than the MC technique.…”
Section: Resultsmentioning
confidence: 91%
“…Calculating organ doses directly from the patient image requires sufficient information about the patient dose and its distribution within the patient [31]. This study aims to determine and investigate the distribution of the dose within a phantom, and to determine the correlation between central, peripheral and weighted size-specific dose for various phantom sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that for fixed setting parameters (kVp, mAs, pitch, etc. ), the patient dose is highly associated with patient size [12,13], weight [14,15], or body mass index [16,17]. In 2011, the AAPM issued report No.…”
Section: Introductionmentioning
confidence: 99%